2014
DOI: 10.1080/17461391.2014.948077
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between facial temperature changes, end‐exercise affect and during‐exercise changes in affect: A preliminary study

Abstract: The present study was performed as an evaluation of the relationships between changes in facial temperature and self-reported pleasure-displeasure during an acute aerobic exercise bout. Ninety-two students performed a 10-minute long session of cycle ergometry at 80-85% of age-predicted maximal heart rate. Using infrared thermography and a single-item measure of pleasure-displeasure (the Feeling Scale, FS), facial temperature and the FS score were sampled at the beginning (Min1:00) and at the end of the exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Although a number of studies conducted during the 80s and the 90s resulted in very little support for the thermogenic hypothesis (e.g., Youngstedt, Dishman, Cureton, & Peacock, 1993), recent investigations have suggested that differences in body temperature during exercise are associated with different changes in affective responses during and immediately after exercising (Magnan, Kwan, & Bryan, 2013;Legrand, Bertucci, & Arfaoui, 2014). To the best of our knowledge, no research specifically examining the link between gender differences in thermoregulation and their association with mood changes following exercise has yet been published; so it would be an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies conducted during the 80s and the 90s resulted in very little support for the thermogenic hypothesis (e.g., Youngstedt, Dishman, Cureton, & Peacock, 1993), recent investigations have suggested that differences in body temperature during exercise are associated with different changes in affective responses during and immediately after exercising (Magnan, Kwan, & Bryan, 2013;Legrand, Bertucci, & Arfaoui, 2014). To the best of our knowledge, no research specifically examining the link between gender differences in thermoregulation and their association with mood changes following exercise has yet been published; so it would be an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared Thermography-a Flir E60 thermal imager (19,200 pixels and 320 × 240 resolution) and FLIR Tools software were used. The regions of interest (ROIs) chosen to analyze the participants' thermal changes were the tip of the nose, cheeks, and chin, as they are considered important facial reference points for capturing emotions (Nhan and Chau 2010; Robinson et al 2012;Ioannou et al 2014;Legrand et al 2015;Salazar-López et al 2015;Cruz-Albarran et al 2017;Kosonogov et al 2017;Goulart et al 2019;Zhang et al 2019).…”
Section: Tools For Evaluating the Psychophysiological Elementsmentioning
confidence: 99%
“…Emotional changes can be stimulated as described elsewhere (24). The facial temperature can also be used as an indicator of enjoyment during exercise, and students could relate the changes in temperature to changes in the perceived effort during the activity (14). Both responses are related to autonomic responses to exercise that are triggered by the onset of sensations (10).…”
Section: Recommendations For the Use Of Irt In Human Physiology Practmentioning
confidence: 99%